(untitled) (Research, Society and Development, 2022)
Introduction: The high frequency generator (HF) employs ozone in the treatment of health systems, producing heat, increasing peripheral vasodilation, cellular metabolism and the local technical repair process. However, there is still no protocol for the parameters in the current literature. Objective: To evaluate the tissue repair process in cleaning processes of different parameters of PA intensity and time. Methodology: Prospective, analytical, interventional, multicenter, experimental, controlling and randomized study. Thirty-five Wistar rats were used, divided into seven groups of five animals each, as follows: six experimental groups and one group. 1, were treated once a lesion with a consecutive diameter punch. Macroscopic analysis was performed, through photographic records of the wound area and microscopic analysis through histological slides. Research approved by the Ethics Committee for the Use of Animals of the Universidade do Estado do Pará, protocol n° 39/20. Results: The morphometric results had a significant reduction of the lesion area in the groups treated by 60 mediums with low and medium. In addition, it was found that a high intensity had a negative effect on the technical repair process. Conclusion: The choice of resource parameters is a repair factor for the use of processless AF. The application with low/medium intensity, for 60 seconds, was the most suitable for the tissue repair process, since it accelerated this process.